Manifestation of Biological, Cognitive Components of the Problem of Creativity - Abdukhakimovna, Odiljonova Aziza (Miasto Przyszłości, 2023)
The article describes the problem of formation and development of creativity. Researches of scientists on determining the sensitive period of creativity formation in children have been analyzed. Researches conducted using different methods of children's standard thinking and creative thinking, information about the period when creativity appears in children are cited. Socio-psychological factors affecting the development of creativity characteristics are expressed.